Rape Culture, Gender Violence, and Religion Interdisciplinary Perspectives (Religion and Radicalism, 2018)
This volume explores the multiple intersections between rape culture, gender violence, and religion. Each chapter considers the ways that religious texts, theologies, and traditions engage with contemporary cultural discourses of gender, sexuality, gender violence, and rape culture. Particularly, they interrogate the multifaceted roles that religious texts and teachings can have in challenging, confirming, querying, or redefining socio-cultural understandings of rape culture and gender violence. Unique to this volume, authors explore the topic from a range of disciplinary perspectives, including anthropology, theology, biblical studies, gender and queer studies, politics, modern history, art history, linguistics, religious studies, and English literature. Together, these interdisciplinary approaches resist the tendency to oversimplify the complexity of the connections between religion, gender violence, and rape culture; rather, the volume offers readers a multi-vocal and multi-perspectival view of this crucial subject, inviting readers to think deeply about it in light of the global crisis of gender violence.